PHYTOCHEMICAL SCREENING, TOXICITY EVALUATION OF POLYCARPAEA CORYMBOSA LAMK AND ITS EFFECT ON CANCER BIOMARKERS OF EHRLICH ASCITES CARCINOMA-INDUCED MICE COMPARED WITH THE REFERENCE STANDARD DRUG 5- FLUOROURACIL - ABIRAMI M, SAKTHI; P, MUTHUSAMY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The current investigation focuses on the study of efficacy of whole plant of Polycarpaea corymbosa Lamk in Ehrlich ascites carcinoma (EAC) inoculated Swiss albino mice. Methods: The whole plant of P. corymbosa Lamk (WPC) was extracted with solvents of increasing polarity and their percentage yields were calculated. The major phytoconstituents present in the plant extracts were determined by standard chemical tests. Tumor was induced in mice by intraperitoneal injection of EAC cells (1×106 cells/mouse). The in vivo antitumor effect of extracts was assessed by monitoring the mean survival time, tumor volume, effect on hematological parameters, determination of lysosome specific cancer markers (cathepsin-D), β-D glucuronidase and acid phosphatase, liver marker enzymes (5’-nuclotidase and lactate dehydrogenase), membrane bound ATPase (Na+/K+ ATPase and Mg2+ ATPase), DNA, and RNA content. Results: The percentage yield obtained were 9.87%w/w, 7.88%w/w, and 16.56% w/w for petroleum ether, ethyl acetate, and ethanol extract, respectively. The phytochemical screenings of those extracts were performed. The order of activity of extracts was ethanol extract > ethyl acetate > petroleum ether. Among the extracts, Ethanol extract of P. corymbosa Lamk. showed a significant increase in life span and decrease in viable cancer cell number and tumor volume. The protective effect of the extract on the hemopoietic system at the dose 200mg∕kg was noted. The alterations in the hematological profile, lysosome-specific cancer markers, liver-specific cancer markers, and membrane-bound ATPases DNA and RNA were restored. Conclusion: The ethanolic extract of P. corymbosa Lamk. possesses in vivo anticancer activity when compared to the tumor control group.